Description of physical activity and screen time among U.S. middle school students - Mi Zhou; Zikun Zhao; Xiaoran Li; Yanxuan Jin; Xinlei Hong; Haoning He; Mengchu Zhao; Xiaomei Song (PLoS ONE, 2025)
Background Physical activity (PA) is important for students in secondary school, however, trends in PA among secondary school students have shown a significant decline. There is a need to understand the PA of middle school students. Objective The first objective is to identify the PA levels and screen time of students in middle school. The second objective of the study is to examine the PA levels and screen time among students of different genders. Methods Participants from four consecutive two-year cycles of National Health and Nutrition Examination Survey (NHANES, 2011–2012, 2013–2014, 2015–2016, and 2017–2018) were included in this study. Spearman correlation model was used to identify the correlation between participants’ demographics, PA, and screen time data. Negative binomial regression model was used to describe students’ PA and screen time (Dependent variable) in different grades (Independent variables). Gender and Age were taken as control variables. Results After the data preprocessing, 2516 participants were included in this study. A significant correlation has been found between grade and PA, instead of screen time. Negative binomial regression shows that students have the lowest PA in their transition year grade 6, and their screen time decreased with the grade increased. Significant differences can be found across gender. Future efforts should focus on developing school transition support programs designed to improve PA.